GR 290 (Romano’s star): II. Light history and evolutionary state - Polcaro, Vito Francesco; Pasquali, Anna (The astronomical journal, 2016)
We have investigated the past light history of the luminous variable star GR 290 (M33/V532, Romano’s Star) in the M33 galaxy, and collected new spectrophotometric observations in order to analyze links between this object, the LBV category, and the Wolf-Rayet stars of the nitrogen sequence. We have built the historical light curve of GR 290 back to 1901, from old observations of the star found in several archival plates of M33. These old recordings together with published and new data on the star allowed us to infer that for at least half a century the star was in a low luminosity state, with B ≃ 18-19, most likely without brighter luminosity phases. After 1960, five large variability cycles of visual luminosity were recorded. The amplitude of the oscillations was seen increasing toward the 1992-1994 maximum, then decreasing during the last maxima. The recent light curve indicates that the photometric variations have been quite similar in all the bands and that the B - V color index has been constant within ±0.1 m despite the 1.5 m change of the visual luminosity. The spectrum of GR 290 at the large maximum of 1992-94 was equivalent to late-B-type, while, during 2002-2014, it varied between WN10h-11h near the visual maxima to WN8h-9h at the luminosity minima. We have detected, during this same period, a clear anti-correlation between the visual luminosity, the strength of the He ii 4686 Å emission line, the strength of the 4600-4700 Å lines’ blend, and the spectral type. From a model analysis of the spectra collected during the whole 2002-2014 period, we find that the Rosseland radius R 2/3 , changed between the minimum and maximum luminosity phases by a factor of three while T eff varied between about 33,000 and 23,000 K. We confirm that the bolometric luminosity of the star has not been constant, but has increased by a factor of ∼1.5 between minimum and maximum luminosity, in phase with the apparent luminosity variations. Presently, GR 290 falls in the H-R diagram close to WN8h stars and is probably younger than them. In the light of current evolutionary models of very massive stars, we find that GR 290 has evolved from an ∼60 M ☉ progenitor star and should have an age of about four million years. From its physical charcteristics, we argue that GR 290 has left the LBV stage and is presently moving from the LBV stage to a Wolf-Rayet stage of a late nitrogen spectral type.